FISH DIVERSITY OF SORODA RESERVOIR, GANJAM, ODISHA - N.K. SIAL; G.C. KUND; S.K. PATRA (The Bioscan, 2024)
A total of 21 fish species were recorded from Soroda reservoir belonging to family Cyprinidae (9species), Siluridae (3species), Channidae (2pecies), Cobitidae (1species), Mastacembalidae (1species), Gobiidae (1species), Ambasidae (1species), Bagridae (1species), Heteropneustidae (1species), and Notopteridae (1species) during the year, 2022-23. The diversity index ranged from 0.03 to 0.09, 1.03 to 1.27 and 11.60 to 13.68 through the Simpson diversity index, Shannon-Weiner diversity index and Margalef diversity index respectively. This study should be considered as a baseline data for more detailed research on the biodiversity of the reservoir. To maintain the species richness and diversity of the reservoir, management should take a precautionary approach and instigate conservation measures that would benefit both the reservoir and the local fishermen.